Giuseppina Ciuffreda, a Concrete Utopian. Issue 4 (1st October 2016) - Ricoveri, Giovanna
ABSTRACT: The following paper describes the life and thought of Giuseppina Ciuffreda, long-time journalist for il manifesto, as well as her contributions to the development of left environmental thinking and movements. She has approached all these themes from a gender point of view, well beyond all schemes and ideologies that infest politics. She has been a protagonist and a precursor to the transition from an old anthropocentric world to a biocentric future.